O tempo e o vento e a tessitura das memórias - Conceição, Francisco Mateus (2016)
The present thesis analyzes the role of memory in the book O Tempo e o Vento considering it as a structuring tool in the narrative. The memory constitutes the novel playing a crucial role in the articulation between the chapters and also within them. Based on Paul Ricouer, it is understood that memory cannot be disassociated from oblivion, which presupposes shadowed zones and incompletion, elements that are strengthened in Erico Verissimo's writing. The trilogy approaches, literarily, a social memory that endures its dusk by narrating the path outlined throughout two thousand years of the Rio Grande do Sul history, the state's different hues, and its relationship with oblivion, its receivers and transmitters. Furthermore, by means of the metafictional expedient, the trilogy focuses on the comings and goings of memory in relation to the writing process.